Study of Nastar Abolecam as a Healthy Snack Alternative for Women of Childbearing Age to Prevent Stunting - Indriyani, Reni; Nadimin, Nadimin; Fatmawaty, Fatmawaty; Hendrayat, Hendrayat (NHM PRESS, 2024)
Introduction: Stunting is a serious issue in Indonesia, particularly in rural areas (34.8%) compared to urban areas (27.3%), caused by a lack of nutritional knowledge among women of reproductive age. The aim of the research is to develop Nastar Abolecam to improve the nutritional intake of women of reproductive age in order to prevent stunting by providing a healthy, nutrient-rich snack. Method: This research employs an experimental design with three variations of Nastar Abolecam formula, comparing ratios of red bean flour and wheat flour (25%, 50%, and 75%). It involves an organoleptic test by 75 panelists of women of reproductive age, as well as analyzing the nutritional value and food cost to determine the product's selling price. Results: The results showed that formula 2 of Nastar Abolecam with catfish floss was the most preferred by panelists in the hedonic test. This formula excels in color, aroma, taste, and texture, with the highest value on the Likert scale. These findings align with previous studies that show consumer preference for products with attractive visual characteristics, a distinctive buttery aroma, a savory taste, and a crunchy texture. Analysis of nutritional content also shows that formula 2 contains good nutrition, including increased iron, so it has the potential to be a healthy snack for pregnant women. With affordable food costs, formula 2 is expected to be well-accepted in the market and contribute to preventing stunting. Conclusion: Formula 2 of Nastar Abolecam with catfish floss proved to be the most preferred by panelists, indicating the success of the combination of ingredients and proportions in meeting consumer preferences. Manufacturers are advised to adopt Formula 2 in large-scale production and conduct further research to develop product variations and improve quality through innovation of raw materials and processing techniques.